Comprehensive experimental and theoretical study of high-speed entry into water and movement of supercavitating strikers at gunfire start - Ishchenko, Aleksandr N.; Burkin, Viktor V.; Korolkov, Leonid V.; Diachkovskii, Alexei S.; Rogaev, Konstantin S.; Bondarchuk, Ivan S.; Sammel, Anton Yu; Sidorov, Alexey D.; Stepanov, Evgeniy Yu; Chupashev, Andrey V.; Kasimov, Vladimir Z. (Behavior of materials under impact, explosion, high pressures and dynamic strain rates)
This paper presents the capabilities of a hydroballistic stand to carry out comprehensive experimental and theoretical studies of high-speed water entry and motion in it of supercavitating strikers during cannon launches. The main technical solutions developed and applied in the study of high-speed throwing of one or several supercavitating strikers are presented. The following processes can be investigated on the hydroballistic stand: acceleration of an inert striker or group of strikers in the ballistic barrel channel in a given mode and obtaining the required initial velocity; movement of strikers on the air part of the ballistic track and separation of the leading devices; entry into the water under different conditions; motion of inert strikers in the water environment; mutual influence of strikers on trajectories in case of group movement; interaction of inert strikers with underwater obstacles. To study and analyze the processes in each of the research areas, mathematical models and software packages have been developed to describe with high accuracy the processes accompanying high-speed throwing, motion and interaction of a single striker or a group of supercavitating strikers in water, as well as with various underwater obstacles.